Self-financing environmental mechanisms - Breitscheidel, Jörg; Gersbach, Hans (CESifo working papers, 2005)
We explore the design of self-financing tax/subsidy mechanisms to solve hold-up problems in environmental regulation. Under Cournot competition, announcing the subsidy rate seems to be preferable to announcing the tax rate. Moreover, for constant marginal damage the hold-up problem can always be solved by setting subsidies. Under Bertrand competition, only announcing the tax rate can induce at least one firm to invest. We suggest that feebate systems in the automotive sector should be designed as self-financing tax/subsidy mechanisms.
Keywords: Arbeitspapier; Graue Literatur